2013
DOI: 10.1371/journal.pgen.1003350
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Mutation in the Upstream Open Reading Frame of the CDKN1B Gene Causes a MEN4 Phenotype

Abstract: The CDKN1B gene encodes the cyclin-dependent kinase inhibitor p27KIP1, an atypical tumor suppressor playing a key role in cell cycle regulation, cell proliferation, and differentiation. Impaired p27KIP1 expression and/or localization are often observed in tumor cells, further confirming its central role in regulating the cell cycle. Recently, germline mutations in CDKN1B have been associated with the inherited multiple endocrine neoplasia syndrome type 4, an autosomal dominant syndrome characterized by varying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
107
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(112 citation statements)
references
References 43 publications
4
107
0
1
Order By: Relevance
“…Following this original description, other patients presenting with a MEN1 phenotype, but no germline mutations in the MEN1 gene, were described (1,4,10). In the evaluated cases, CDKN1B gene mutations generate a decrease in its encoded product, through various mechanisms, encompassing the synthesis of a truncated protein and/or the reduction of either protein expression (4,5,6,8). One of the identified mutations consists of a nucleotide variation at a stop codon associated with the formation of a protein longer than normal, mostly localized in the cytoplasm rather than in the nucleus, with a low stability and a reduced CDK2 binding affinity (1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Following this original description, other patients presenting with a MEN1 phenotype, but no germline mutations in the MEN1 gene, were described (1,4,10). In the evaluated cases, CDKN1B gene mutations generate a decrease in its encoded product, through various mechanisms, encompassing the synthesis of a truncated protein and/or the reduction of either protein expression (4,5,6,8). One of the identified mutations consists of a nucleotide variation at a stop codon associated with the formation of a protein longer than normal, mostly localized in the cytoplasm rather than in the nucleus, with a low stability and a reduced CDK2 binding affinity (1).…”
Section: Discussionmentioning
confidence: 99%
“…PHPT has a high penetrance in MEN4 and, similar to MEN1, is the first diagnosed endocrinopathy in most cases, but with an age at onset more than two decades later than in MEN1 (mean 56 years in MEN4 vs 20-25 years in MEN1) (1,4,5,6,7,8). In about half of the MEN4 patients, only one gland was affected and responsible for PHPT, without genotype/phenotype relationships ever described regarding the severity and the number of the involved parathyroids (1,4,5,6,7,8). The follow-up of these patients is often lacking, and no information on the persistence or recurrence of PHPT is usually referred.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A pathogenic truncating mutation in the human orthologue CDKN1B was identified in a 48-year-old woman with a personal history of acromegaly and primary hyperparathyroidism and a family history of renal Printed in Great Britain angiomyolipoma in a confirmed mutation carrier (Pellegata et al 2006). Subsequently, a number of cases of both functional (Georgitsi et al 2007, Agarwal et al 2009, Tichomirowa et al 2012, Occhi et al 2013, Sambugaro et al 2015 and non-functional (Molatore et al 2010) PAs have been reported in patients with germline mutations in CDKN1B, although they account for only a minority of MEN1 mutation negative patients (Ozawa et al 2007, Igreja et al 2009). Mutations in other cyclin-dependent kinase inhibitors have also been linked to MEN.…”
Section: Men4mentioning
confidence: 99%
“…The defect led to a reduction in CDKN1B mRNA levels, altered secondary mRNA structure, and reduced transcriptional activity of the gene in laboratory studies [14]. The report by Sambugaro and Di Ruvo et al follows the identification of another 4-bp deletion (c.-456_-453delCCTT) in a highly conserved regulatory region of the 5 0 UTR of the CDKN1B gene in a patient with a pituitary adenoma and a well-differentiated pancreatic neoplasm [15].…”
mentioning
confidence: 97%